Manajemen Kearsipan Dalam Meningkatkan Mutu Layanan Administrasi Di SMA Negeri 2 Luwu - Namira Putri Andini; Taqwa; Firman Patawari; Tasdin Tahrim (Hikamatzu | Journal of Multidisciplinary, 2024)
This journal discusses archival management in improving the quality of administrative services at SMA Negeri 2 Luwu. This study aims to determine how the implementation of archival management is carried out at SMA Negeri 2 Luwu and what are the obstacles to archival management in improving the quality of administrative services at SMA Negeri 2 Luwu. The type of research used in this research is descriptive qualitative with a phenomenological approach. Data sources consist of primary data and secondary data, with data collection techniques consisting of observation, interviews, and documentation. Data analysis was carried out with three stages, namely data reduction, data presentation, and conclusion drawing. The research results show that archive creation uses a format that already exists in schools, archive management uses an alphabetical sistem and sequential numbers, uses a predetermined classification list from the school, and uses an agenda book to identify archives. Then the archive retrieval procedure uses a manual method, namely searching for the archive on the computer first, if the archive has been destroyed then looking for the archive in the archive storage cabinet by looking at the archive code in the agenda book. Finally, the archive shrinkage procedure is carried out when the archives have accumulated, the destroyed archives are archives that no longer have any use value, this archive shrinkage is carried out by burning. And the obstacles found include the lack of expert human resources in managing archives, the lack of facilities and infrastructure, and the lack of services obtained from the administrative field.